The Effect Of Non Performing Loan, Loan To Deposit Ratio And Third Party Funds On Profitability During The Covid-19 Pandemic In Government Banking - Diska Nindi Saputri; Nisa Mutiara (Otonomi, 2021)
The problem of this research is about financial management with a focus on the problem of non-performing loans. Loan to deposit ratio and third party funds related to the problem of fluctuations in asset growth and its effect on profitability as measured by return on assets. The population in this study were 4 government-owned banks during the COVID-19 pandemic period in March 2020 - February 2021. The number of observation samples is 48 data, with a statistical analysis approach through statistical descriptive, classical assumption test and multiple linear regression test. The results of this study indicate that: (1) There is a partial positive and significant effect of NPL on ROA profitability. (2) There is a partial positive and significant effect of LDR on ROA profitability. (3) There is a partial positive and significant effect of TPF on ROA Profitability. (4) NPL, LDR and DPK are able to simultaneously influence the ROA of government-owned banks during the covid 19 pandemic, the percentage contribution of the influence of NPL, LDR and DPK is 43.3% in relation to company profitability during the current covid 19 pandemic.